2019
DOI: 10.3389/fimmu.2019.00059
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Targeting Using a DNA Vaccine Induces Specific Antibodies and CD4+ T Cells to the Dengue Virus Envelope Protein Domain III

Abstract: Dengue fever has become a global threat, causing millions of infections every year. An effective vaccine against all four serotypes of dengue virus (DENV) has not been developed yet. Among the different vaccination strategies available today, DNA vaccines are safe and practical, but currently induce relatively weak immune responses in humans. In order to improve immunogenicity, antigens may be targeted to dendritic cells (DCs), the main antigen presenting cells and orchestrators of the adaptive immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 85 publications
(112 reference statements)
0
36
0
Order By: Relevance
“…The uniqueness of the B cell-based vaccine approach is that antigens targeted to B cells elicit exaggerated Ag-specific Ab responses, although targeting antigens to dendritic cells (DCs) via lectins such as DEC205 has been shown to indirectly promote B cell humoral responses. 33 When DCs capture antigens to induce Ab responses, antigens are digested and dominant epitopes are presented on the surface as MHC class I or class II molecules. 34,35 The generation of blocking antibodies requires the presentation of intact Ag to B cells.…”
Section: Discussionmentioning
confidence: 99%
“…The uniqueness of the B cell-based vaccine approach is that antigens targeted to B cells elicit exaggerated Ag-specific Ab responses, although targeting antigens to dendritic cells (DCs) via lectins such as DEC205 has been shown to indirectly promote B cell humoral responses. 33 When DCs capture antigens to induce Ab responses, antigens are digested and dominant epitopes are presented on the surface as MHC class I or class II molecules. 34,35 The generation of blocking antibodies requires the presentation of intact Ag to B cells.…”
Section: Discussionmentioning
confidence: 99%
“…The E protein has three domains(I-III). Domain III contains serotype-specific epitopes that can elicit neutralizing antibodies and the host cell receptor recognition site that subserve viral attach and entry into host cell [40][41][42], EDIII is widely used in vaccine development for it can induce antibodies against DENV infection [42][43][44]. Kawano et al study found that the amino acid residue located in E155(DI region) of DENV-4 converted from T to I change virulence of the virus [45], our previous study also find the E155 amino acid of DENV-1 change from I to T may cause a weak in viral virulence [25].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, 21 possible protein binding sites (including 87, 93, 97, 120, 157, 184, 198, 199, 200, 357, 376, 377, 503, 505, 507, 508, 509, 595, 622, 623, 642) were all found in MN123849, MN123854 and DEN-1SS. However, there are 9 and 10 sites were lost in MN123849 (5,7,158,195,197,365,366,429,621) and MN123854 (5,7,40,41,123,195 Approximately 8 and 5 distinct changes were found in the helical, respectively, and few changes observed in disordered region. Some difference observed in helical transmembrane regions between DEN-1SS and MN123849, MN123854 strains (Fig.4).…”
Section: Possible Secondary Structure Of Structural Protein Regionsmentioning
confidence: 97%
“…For example, integrating antigen sequence into lysosomal membrane protein increases the expression of MHC class II antigens, thereby enhancing the production of CD4 T cells and anti-CD4 antigens and ultimately improving the immunogenicity of the DENV2 prM/E DNA vaccine [98]. A DNA vaccine expressing an antigen fused with a single-chain Fv antibody (scFv) specific for the DC endocytic receptor DEC205 could induce a strong immune response to the target antigen [99].…”
Section: Dna Vaccinesmentioning
confidence: 99%